The critical role of aggregate microstructure in thermal shock resistance and slag resistance of Al2O3–SiC–C castable. Issue 8 (15th April 2022) - Ma, Jiuhong; Zhao, Huizhong; Yu, Jun; Zhang, Han; Li, Yichong; Shi, Lida; Zhao, Yi; He, Jian
Abstract: In this study, four types of commercial tabular corundum were selected as aggregates, and four Al2 O3 –SiC–C castables were prepared under same conditions. The microstructure characteristics of the aggregates were observed. The thermal shock resistance and slag resistance mechanism were evaluated. Dendritic pores were proven to be beneficial for relieving and guiding thermal stress. According to the Lobe method, the dendritic pores provided the aggregates with a higher thermal conductivity and better thermal stability than the circular pores. The role of the aggregate microstructure in resisting slag erosion was discussed through thermodynamic and kinetic analyses. The presence of dendritic pores and a small neck size led to a faster dissolution rate during the slag erosion process. At the same time, the dissolution rate and dissolution amount increased, resulting in the faster supersaturation of the slag. Based on Ostwald's supersaturation theory, a thicker spinel isolation layer would be precipitated on the inner walls of the slag erosion path, thereby preventing the further erosion of the slag.